Gender, homicide, and the politics of responsibility fatal relationships - Gore, Ashlee (Feminist criminology, 2022)
Gender, Homicide, and the Politics of Responsibility book explores the competing and contradictory understandings of violence against women and men's responsibility, situating these within the personal and political intersections of neoliberal and 'postfeminist' imperatives of individualisation, choice, and empowerment. As violence against women has become a national and international policy priority, feminist concerns about violence against women and men's responsibility, have entered the mainstream only to be articulated in politically contradictory ways. This book explores themes of responsibility for violence, and the social and legal consequences that men and women uniquely or differently encounter. By drawing on high-profile cases of homicide, an extensive literature on feminist perspectives on violence, and compelling focus group discussions, the book examines the politicised claims regarding the 'responsibility' of men and women as both victims and offenders in intimate relationships. Deploying a range of interdisciplinary approaches, it utilises a blend of cultural theory and psychosocial analysis to offer an account of the infiltration of postfeminist and neoliberal sensibilities of individualism and responsibilisation in the social, legal, and interpersonal imaginary. The book makes contributions to several fields, such as the current public policy initiatives to hold men accountable for violence against women; understanding public attitudes to violence against women; and contextualising the challenges faced by a number of feminist reforms that seek to address these issues. An accessible and compelling read, Gender, Homicide, and the Politics of Responsibility will appeal to students and scholars of criminology, sociology, gender studies and those interested in understanding the debates surrounding violence against women, violence by women, and the social construction of responsibility and responsibilisation"--